Adaptation of midwifery education curriculum in the fourth industrial revolution - Septi Aruani; Ari Indra Susanti (Curricula: Journal of Curriculum Development, 2025)
The evolution of technology in the Fourth Industrial Revolution age requires the world of education to undergo digital metamorphosis, including midwifery education. In producing graduates who are not only clinically competent but also able to adapt to technological advances, the midwifery curriculum needs to be improved. This study aims to examine the adaptation strategy for the midwifery education curriculum in response to the challenges and opportunities presented by the Fourth Industrial Revolution. The limited literature examining digital technology collaboration in midwifery education provides the background and driving force behind this research. The approach employed is a literature review using a qualitative descriptive method, examining eight relevant scientific articles published between 2020-2025. The results of the study show that integration has been proven to improve the quality of learning and student competence. Challenges such as limited infrastructure, educators' digital literacy, and institutional readiness remain the primary obstacles. Curriculum reform based on Outcome-Based Education and cross-sector collaboration are the keys to adapting midwifery education to remain relevant, professional, and humanistic in the digital age.   Abstrak Evolusi teknologi di era Revolusi Industri Keempat menuntut dunia pendidikan untuk bertransformasi secara digital, termasuk dalam pendidikan kebidanan sehingga menghasilkan lulusan yang kompeten secara klinis, mampu beradaptasi dengan kemajuan teknologi. Maka dari itu, perlu adanya pembenahan dalam kurikulum kebidanan. Penelitian ini bertujuan untuk mengkaji strategi adaptasi kurikulum pendidikan kebidanan dalam menghadapi tantangan dan peluang yang muncul akibat perkembangan teknologi. Keterbatasan literatur yang membahas kolaborasi teknologi digital dalam pendidikan kebidanan menjadi latar belakang penting bagi penelitian ini. Pendekatan yang digunakan adalah tinjauan literatur dengan metode deskriptif kualitatif, yang menganalisis delapan artikel ilmiah terbitan tahun 2020-2025. Hasil penelitian menunjukkan bahwa integrasi teknologi dalam pendidikan kebidanan terbukti meningkatkan kualitas pembelajaran, kompetensi mahasiswa, dan kesiapan mereka menghadapi tantangan profesi. Namun, tantangan seperti keterbatasan infrastruktur, rendahnya literasi digital pendidik, dan kesiapan institusi masih menjadi hambatan utama. Reformasi kurikulum berbasis Outcome-Based Education dan kerja sama lintas sektor sangat diperlukan untuk memastikan pendidikan kebidanan tetap relevan, profesional, dan humanistik di era digital. Kata Kunci: adaptasi pendidikan; kurikulum kebidanan; perubahan digital; revolusi industri keempat